Paediatric genomic testing: Navigating genomic reports for the general paediatrician. (23rd August 2021) - Shah, Margit; Selvanathan, Arthavan; Baynam, Gareth; Berman, Yemima; Boughtwood, Tiffany; Freckmann, Mary‐Louise; Parasivam, Gayathri; White, Susan M; Grainger, Natalie; Kirk, Edwin P; Ma, Alan SL; Sachdev, Rani
Abstract : Monogenic rare disorders contribute significantly to paediatric morbidity and mortality, and elucidation of the underlying genetic cause may have benefits for patients, families and clinicians. Advances in genomic technology have enabled diagnostic yields of up to 50% in some paediatric cohorts. This has led to an increase in the uptake of genetic testing across paediatric disciplines. This can place an increased burden on paediatricians, who may now be responsible for interpreting and explaining test results to patients. However, genomic results can be complex, and sometimes inconclusive for the ordering paediatrician. Results may also cause uncertainty and anxiety for patients and their families. The paediatrician's genetic literacy and knowledge of genetic principles are therefore critical to inform discussions with families and guide ongoing patient care. Here, we present four hypothetical case vignettes where genomic testing is undertaken, and discuss possible results and their implications for paediatricians and families. We also provide a list of key terms for paediatricians.